2020
DOI: 10.1002/chem.201904584
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective, Amine‐Derived Cannabinoid Receptor 2 Probes

Abstract: The endocannabinoid (eCB) system is implied in various human diseases ranging from central nervous system to autoimmune disorders. Cannabinoid receptor 2 (CB2R) is an integral component of the eCB system. Yet, the downstream effects elicited by this G protein‐coupled receptor upon binding of endogenous or synthetic ligands are insufficiently understood—likely due to the limited arsenal of reliable biological and chemical tools. Herein, we report the design and synthesis of CB2R‐selective cannabinoids along wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…In addition, the model predicts a hydrogen-bond between the amide-proton of 3b and the carbonyl oxygen of Ser90, which contributes to the high affinity of the probe. 39 When the docking pose of 3b was compared with the recently published co-crystal structure of active state CB2R in complex with agonist WIN55,212-2 48 the binding mode of the docked core motif was found to be identical, and the hydrogen bond with Ser90 was maintained.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the model predicts a hydrogen-bond between the amide-proton of 3b and the carbonyl oxygen of Ser90, which contributes to the high affinity of the probe. 39 When the docking pose of 3b was compared with the recently published co-crystal structure of active state CB2R in complex with agonist WIN55,212-2 48 the binding mode of the docked core motif was found to be identical, and the hydrogen bond with Ser90 was maintained.…”
Section: Resultsmentioning
confidence: 97%
“…With a high-affinity recognition element, such as 1, 39 as a starting point, choice of the exit vector and linker-type for fluorophore attachment are the main challenges to ensure high probe affinity and selectivity. 40,41 Our preliminary synthetic studies with 2 suggested a strategy for a family of fluorescent probes.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, replacement of the allylic alcohol in HU308 with an amide linkage enabled attachment of fluorescent dyes and led to highly specific probes. 31,32, A wide range of substituents are tolerated at this position without affecting affinity as they extend out of the orthosteric binding pocket of CB2. By contrast, optical control over receptor activity requires identification of a different locus for photoswitch conjugation.…”
Section: Design Synthesis and Characterization Of Photoswitchable Hmentioning
confidence: 99%
“…1). 31,32 Azobenzenes are the presently preferred switch in photopharmacology. 33 We devised three photoswitchable HU308 derivatives harboring azobenzenes.…”
Section: Design Synthesis and Characterization Of Photoswitchable Hmentioning
confidence: 99%
“…Their ability to bind different streptavidin tags made them suitable to study and visualize CBRs in native systems [170]. Moreover, several CB2-specific probes based on photoaffinity and fluorescent labelling have also been developed [171][172][173][174][175]. Their capacity to track CB2 in various cell types and settings may be of quite some interest in studies monitoring the expression of CB2 and its interactions in biological systems (Table 2).…”
Section: Chemical Probes For Ecs Researchmentioning
confidence: 99%